Effect of commonly used EOR polymers on low concentration surfactant phase behaviors. (15th February 2021) - Zhang, Guoyin; Yu, Jianjia
Abstract: High molecular weight polymers are required for the purpose of mobility and conformance control during surfactant chemical flooding. However, they are usually not incorporated in the process of phase behavior tests to screen surfactant formulations. Literature review shows some particular polymers have a boosting effect on surfactant solubilization efficiency. To gain more insight into this subject, we performed phase behavior tests in the presence of four commonly used EOR polymers for low concentration surfactant systems (0.3%). They were two partially hydrolyzed polyacrylamides (HPAM) with different molecular weights, one xanthan gum, and one hydrophobically associating polymer (HAP). Their influence on the optimal salinity, solubilization ratio, quickness of phase equilibration, and middle phase rheological behavior was assessed. The results showed: (1) a decrease of surfactant solubilization efficiency and the optimal salinity was observed with HPAM polymers. This trend became more pronounced as increase of polymer concentration and molecular weight; (2) xanthan seemed to slightly increase the optimal salinity without significantly affecting middle phase volume; (3) both HPAM and xanthan did not delay or quicken the equilibration of various phases compared to the zero polymer case. The analysis of the oil/water solubilization ratios showed HPAM tended to drag water out of the middle phase, while the presence of xanthan increased the water solubilization in the middle phase; (4) the viscosity and rheology of the middle phase microemulsions were very similar for systems containing HPAM, xanthan, and zero polymer. This confirmed the partitioning of polymer molecules in the middle phase was negligible; (5) the association of HAP with surfactants thickened the surfactant-rich phase, which made the phase separation dramatically slow. These phenomena could be explained well by the nature of their molecular structures. For both water-soluble HPAM and xanthan gum, unlike the reported diblock copolymers, they lack the amphiphilic features, which prevents them from adsorbing in the surfactant film. Conversely, the introduction of hydrophobic group into the backbone renders associating polymers some surfactant-like attributes, enabling them to associate with surfactant molecules and affect the surfactant-rich phase behaviors.